Detailed kinetic study of cumene isopropylation in a liquid-liquid biphasic system using acidic chloroaluminate ionic liquids. - Joni, Joni; Schmitt, Daniel; Schulz, Peter; Lotz, T. J.; Wasserscheid, Peter (Journal of Catalysis, 2008)
A kinetic study of cumene isopropylation has been carried out using the acidic ionic liq. 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl)/AlCl3 (molar ratio 1:2) as the catalyst phase in a semi-batch liq.-liq. biphasic reaction system. Kinetic models representing the alkylation reaction network have been established based on reaction temp. and propylene partial pressure variations. By comparing the results of the kinetic models with the measured concns. in the liq. org. phase, the importance of the different product solubilities in the acidic ionic liq. became evident. Correction of the product concns. in the org. phase based on a COSMO-RS calcn. of the relative product solubilities in the acidic ionic liq. [EMIM][Al2Cl7] gave a remarkably good prediction of the reaction kinetics by the kinetic model. These findings demonstrate the suitability of COSMO-RS to predict the relative solubilities of different arom. compds. in highly reactive catalytic systems. [on SciFinder(R)]
Keywords: cumene isopropylation kinetics biphasic system acidic chloroaluminate ionic liq